Design of resilient and viable sourcing strategies in intertwined circular supply networks - Khadija Echefaj; Abdelkabir Charkaoui; Anass Cherrafi; Dmitry Ivanov (Annals of Operations Research, 2024)
This study examines the effects of intertwining and circularity on the design of resilient and viable sourcing and recovery strategies in supply chains. We first construct a case study where the supply chains of three industries (i.e., automotive, healthcare, and electronics) frame an intertwined supply network (ISN). Through a discrete-event simulation model developed in anyLogistix, we examine the impact of disruptions in supply and demand on the performance of individual supply chains and the ISN as a whole. We test the performance of several sourcing strategies and their combinations. A special focus is directed toward shared reverse flows. The results show that disruption impact and recovery processes in the Circular ISN do not always follow conventional patterns known from the resilience of individual supply chains due to intertwining and circularity effects. We offer some managerial recommendations for the design of resilient sourcing strategies in the ISN context that are triangulated around collaborative sourcing practices, coordinated production planning, shared reverse flows, and visibility in inventory management.
Keywords: 000; Sourcing strategy; Intertwined supply network; Resilience; Circular economy; Simulation; anyLogistix